Особливості стану тканин пародонта в дітей-інвалідів із хворобами центральної нервової системи - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2015)
Відомо, що головна причина захворювань тканин пародонта - погана гігієна порожнини рота [1, 2, 3]. За даними МОЗ України, поширеність захворювань тканин пародонта серед населення віком 18-20 років становить 92%, із них 77,5% - запальні та 14,55% - запально-дистрофічні процеси (3,4%). Захворювання тканин пародонта залишаються одними з найпоширеніших стоматологічних хвороб. Маємо цілу низку сучасних публікацій щодо лікування запальних і деструктивних захворювань пародонта [5, 6, 7]. Але їх виконання неможливе в такої категорії пацієнтів, як діти-інваліди з хворобами центральної нервової системи. У цих дітей є серйозні функціональні порушення: спонтанні, непередбачувані рухи, надмірна нервоворефлекторна збудженість. Тому важливим завданням стає своєчасна профілактика стоматологічних захворювань у таких дітей. The article presents the results of investigation of condition of periodontal tissues in 98 children with disabilities aged from 2 to 18 years with diseases of the Central nervous system. High prevalence and intensity of diseases of fabrics of parodont. It is known that the leading cause of periodontal diseases is poor oral hygiene. Periodontal diseases remain among the most common dental diseases. There are a number of modern publications on the treatment of inflammatory and destructive periodontal diseases. But its implementation is impossible in such a category of patients as disabled children with diseases of the central nervous system. Therefore, an important task is the timely prevention of dental diseases in these children. Aim of the research: to study the dental status in disabled children with central nervous system diseases – to examine the state of oral hygiene; to evaluate the status of periodontal tissues; to study the features of dentoalveolar anomalies.
Features of condition of periodontal tissues in disabled children with central nervous system diseases
Keywords: disabled children with diseases of the Central nervous system complicated caries; low level of oral hygiene